The In Dubio Pro Natura Principle in the Enforcement of Environmental Criminal Law in Indonesia: A Case Study of PT Kallista Alam - Nabila Alinka Wibowo; Lucky Kresna Aji (Recidive : Jurnal Hukum Pidana dan Penanggulangan Kejahatan, 2026)
This study examines the application of the principle of in dubio pro natura in environmental law enforcement in Indonesia, focusing on the PT Kallista Alam peatland fire case as reflected in Supreme Court Decision Number 651K/PDT/2015. Using doctrinal research methods through legislative, comparative, and conceptual approaches, this study analyzes the principle's position and its application by judges. The results of the study indicate that, although it has not been explicitly codified, the principle of in dubio pro natura is grounded in the precautionary principle in Article 2, letter f, of Law Number 32 of 2009 and in the constitutional mandate in Article 28H, paragraph (1). Its application has shifted the paradigm from anthropocentrism to ecocentrism. In the PT Kallista Alam case, amid uncertainty about the extent of irreversible damage, the panel of judges progressively prioritized scientific evidence indicating that the land fire reached 1,000 hectares. The judge then sentenced the corporation to pay material compensation and massive recovery costs. This cassation ruling legitimizes the principle of in dubio pro natura as a robust jurisprudential principle for ecosystem sustainability. Harmonization of regulations and standardization of technical guidelines are necessary to reduce disparities in future decisions.